1991
DOI: 10.1016/0002-9343(91)90634-a
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in severe onchocercal skin disease after a single dose of ivermectin

Abstract: Single-dose ivermectin shows promise as the first acceptable treatment for severe onchocercal dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…however, is not affected by ivermectin treatment (Pacqué et al 1991b;Burnham 1995;Kennedy et al 2002).…”
Section: A49mentioning
confidence: 85%
See 1 more Smart Citation
“…however, is not affected by ivermectin treatment (Pacqué et al 1991b;Burnham 1995;Kennedy et al 2002).…”
Section: A49mentioning
confidence: 85%
“…1998b; Ogbuagu & Eneanya 1998). Depigmentation however, is not affected by ivermectin treatment (Pacqué et al. 1991b; Burnham 1995; Kennedy et al.…”
Section: Onchocercal Skin Diseasementioning
confidence: 99%
“…Current evidence on the short-term effect of ivermectin on onchocercal skin disease (OSD) and related itching is conflicting and inconclusive. Although ivermectin reduces microfilarial loads in the skin, previous studies did not find a consistent and clear effect on OSD (Pacque et al 1991;Whitworth et al 1992b;Sumo et al 1993;Burnham 1995) and itching (Sumo et al 1993;Whitworth et al 1992aWhitworth et al , 1996Burnham 1995).…”
Section: Introductionmentioning
confidence: 94%
“…Due to lack of suitable model host for laboratory study, the high cost and ethical consideration for subjecting humans to placebo trial for up to ten years have precluded determination of the outcome of a single treatment. It has been documented by Pacque et al (32) that up to 33% of patients in non-endemic areas were cured with only 1 dose of ivermectin. Thus, the study of treatment compliance rate after a decade of intervention and the observed impact of single dose treatment on skin mf load and nodule rates clearly support the efficacy of single-dose treatment.…”
Section: Discussionmentioning
confidence: 97%